Interstitial lung diseases: course report - Kreuter, Michael; Zeynel, Sead; Mishra, Deebya Raj (Breathe, 2016)
Tweetable abstract ERSpublications - click to tweetERS hosted a 3-day course on interstitial lung diseases in Heidelberg, Germany http://ow.ly/M8MD3021q6n
Gesehen am 28.05.2020